Caregiver capabilities and socio-economic disparities in children’s health-related quality of life - Turner, Georgia (University of the Witwatersrand, Johannesburg, 2024)
This study investigates the relationship between children’s health-related quality of life and the associated contextual factors. Furthermore, this study analyses the socio-economic disparities that exist amongst children and what particular social determinants of health are influencing their health and wellbeing. Using an OLS regression as well as the Blinder-Oaxaca decomposition, the results show how children with a lower socio-economic status experience a lower HRQOL as opposed to those with a higher socio-economic status. Furthermore, this paper reports new research on the association of caregiver’s capabilities and children’s HRQOL which represents an important explanation for children’s health-related quality of life. Caregivers’ capabilities are a set of tools that enables parents to manage work, life and parenting effectively. The results provide evidence how important these capabilities are as it contributes to a better health related quality of life in their children. The findings show how a higher socio-economic status is associated with better caregiver capabilities. This is an important finding in the South African context, as exorbitant social inequalities exist, and hence, improving adult capabilities could potentially result in not only aiding to narrow the socio-economic disparity gap, but also improving the overall quality and health of children. This also leads to the premise of a bi-directional association whereby improving caregivers’ socio-economic status may likely also improve their capabilities.
A research report submitted in fulfillment of the requirements for the Master of Commerce (Applied Development Economics), In the Faculty of Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; socio-economic; CHILDREN’S HEALTH-RELATED; SDG-3: Good health and well-being; SDG-8: Decent work and economic growth